Anterior capsular contraction after cataract surgery in eyes of diabetic patients. Issue 1 (1st January 2001) - Kato, Satoshi; Oshika, Tetsuro; Numaga, Jiro; Hayashi, Yoshie; Oshiro, Miwako; Yuguchi, Takuma; Kaiya, Tadayoshi
Abstract : AIM: To investigate change in the area of anterior capsular opening (ACO) after cataract surgery and its relation to the degree of postoperative anterior inflammation in patients with diabetes mellitus (DM). METHODS: 31 eyes of 31 patients with DM and 30 eyes of 30 normal controls scheduled to undergo cataract surgery were examined prospectively. The area of ACO was measured with an anterior eye segment analysis system (EAS-1000) on the day following surgery and 3, 6, and 12 months after surgery. Comparative analyses were made on the area of ACO relative to the presence of DM and diabetic retinopathy (DR). The percentage reduction of area of ACO was calculated from values 1 day and 12 months after surgery, and multiple regression analysis was performed on the presence of DM, patient age, ACO area on the first postoperative day, and aqueous flare intensity 1 day and 12 months after surgery. RESULTS: The area was significantly smaller in the DM group at 3 (p=0.015, Student's t test), 6 (p=0.011), and 12 (p=0.010) months postoperatively. Patients having DR showed significantly smaller ACO area than the non-DR group 3 (p=0.039), 6 (p=0.033), and 12 (p=0.028) months after surgery. Multiple regression analysis revealed that presence of DM (p=0.003) and aqueous flare intensity 12 months after surgery (p=0.039) significantly correlated with the percentage reduction of area of ACO. Age, ACO area at 1 day postoperatively, and aqueous flare intensity immediately after surgery were not relevant to ACO contraction. CONCLUSIONS: Anterior capsular contraction after cataract surgery was greater in eyes of DM patients, especially in those with DR and increased permeability of the blood-aqueous barrier.